(untitled) (The Research of Medical Science Review, 2025)
Endotracheal intubation using conventional laryngoscopy triggers a haemodynamic response, leading to increased heart rate and blood pressure. There are conflicting reports regarding the haemodynamic stress response differences between conventional Macintosh and video laryngoscopes, with limited studies on cardiac surgical patients. This study aimed to compare the haemodynamic stress response and mean intubation time between video and direct laryngoscopy in patients undergoing coronary artery bypass grafting (CABG) at a tertiary care hospital in Karachi. A randomized controlled trial was conducted at the Department of Anaesthesia, National Institute of Cardiovascular Diseases, Karachi, over six months. Data were prospectively collected from 244 patients who met the inclusion criteria, following verbal consent. Quantitative and qualitative data were analyzed, and a post-stratification chi-square test was applied, with a significance threshold of p ≤ 0.05. Results showed that the mean heart rate was significantly lower in the video laryngoscope group (78.06±6.10) compared to the direct laryngoscope group (84.30±5.14), with a p-value of 0.001. Similarly, the mean arterial pressure was lower in the video laryngoscope group (83.47±2.69) than in the direct laryngoscope group (86±3.58), with a p-value of 0.001. The mean total intubation time was also shorter with video laryngoscopy (22.19±4.33) compared to direct laryngoscopy (24.08±5.91), with a p-value of 0.001. In conclusion, video laryngoscopy offers better haemodynamic stability and ease of intubation than conventional direct laryngoscopy in patients undergoing CABG. These findings suggest that video laryngoscopes may be a superior choice for improving patient safety and procedural efficiency in high-risk cardiac surgeries.